Prepozyci prepozytury Kraśnickiej Kanoników Regularnych Laterańskich od fundacji do reformy w 1628 roku - Łatak, Kazimierz (Saeculum Christianum. Pismo Historyczne, 2018)
This article focuses on the prepositions of the monastery of the Canon Regular of the Lateran in Krasnik from its foundation in May 1468 to the reform of 1620-1627. Founded by Jan Rabsztynski of Teczyn, the owner of Krasnik goods, the monastery was considered as one of the prominent centers in terms of religions, social and cultural activity in the Lublin Region. Therefore, the studying of its history, culture and religious activities are important for getting to know the history of the city and its region. The culture of the monastery influenced the culture of the local environment, while the culture of the surroundings area left traces in the culture and activities of the monastery.